Integrating de novo QTL‐seq and linkage mapping to identify quantitative trait loci conditioning physiological resistance and avoidance to white mold disease in dry bean - Jayanta Roy; Alvaro Soler‐Garzón; Phillip N. Miklas; Rian Lee; Josh Clevenger; Zachary Myers; Walid Korani; Phillip E. McClean (The Plant Genome, 2023)
Abstract White mold (WM), caused by the ubiquitous fungus Sclerotinia sclerotiorum, is a devastating disease that limits production and quality of dry bean globally. In the present study, classic linkage mapping combined with QTL‐seq were employed in two recombinant inbred line (RIL) populations, “Montrose”/I9365‐25 (M25) and “Raven”/I9365‐31 (R31), with the initial goal of fine‐mapping QTL WM5.4 and WM7.5 that condition WM resistance. The RILs were phenotyped for WM reactions under greenhouse (straw test) and field environments. The general region of WM5.4 and WM7.5 were reconfirmed with both mapping strategies within each population. Combining the results from both mapping strategies, WM5.4 was delimited to a 22.60–36.25 Mb interval in the heterochromatic regions on Pv05, while WM7.5 was narrowed to a 0.83 Mb (3.99–4.82 Mb) region on the Pv07 chromosome. Furthermore, additional QTL WM2.2a (3.81–7.24 Mb), WM2.2b (11.18–17.37 Mb, heterochromatic region), and WM2.2c (23.33–25.94 Mb) were mapped to a narrowed genomic interval on Pv02 and WM4.2 in a 0.89 Mb physical interval at the distal end of Pv04 chromosome. Gene models encoding gibberellin 2‐oxidase proteins regulating plant architecture are likely candidate genes associated with WM2.2a resistance. Nine gene models encoding a disease resistance protein (quinone reductase family protein and ATWRKY69) found within the WM5.4 QTL interval are putative candidate genes. Clusters of 13 and 5 copies of gene models encoding cysteine‐rich receptor‐like kinase and receptor‐like protein kinase‐related family proteins, respectively, are potential candidate genes associated with WM7.5 resistance and most likely trigger physiological resistance to WM. Acquired knowledge of the narrowed major QTL intervals, flanking markers, and candidate genes provides promising opportunities to develop functional molecular markers to implement marker‐assisted selection for WM resistant dry bean cultivars.